Construction and design manual. School buildings. - (:unkn) unknown (DOM Publ., 2014)
Safety, flexibility and accessibility: school architecture has become a building task for owners and architects requiring detailed knowledge beyond pedagogy and structural design. In fact, the architectural perception of children and youth has historically been strongly influenced by places of learning and teaching. On the other hand, in the era of digitalization, whether such places are relevant any more for the transfer of knowledge is an open question. This manual takes an architectural view of School Buildings. The authors discuss building typologies, organizational models and development trends. In doing so, more than 30 international school buildings with detailed drawings and photographs are presented. Ten design parameters round off the planning aid for the successful construction of schools in the 21st century.
Keywords: Schule; Schulbau; Schulgebäude; Architektur; Sicherheit; Planungshilfe; Baukonstruktion; Beispielsammlung; Schultyp; Barrierefreiheit